2017
DOI: 10.1016/j.jcps.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A focus on partisanship: How it impacts voting behaviors and political attitudes

Abstract: The target article by John Jost (2017 – this issue) focuses on political ideology (liberalism vs. conservatism) and its association with personal characteristics, cognitive processing style, and motivational interests. Jost's arguments and data are very compelling and will inspire consumer psychologists to do more research in the political domain. To enable this goal further, we complement the target article by focusing on partisanship, another major determinant of political judgments and decisions. Whereas po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 86 publications
(131 reference statements)
1
31
0
Order By: Relevance
“…Conversely, Democrats were more attentive than Republicans to substantive information about policy content. Krishna and Sokolova (2017) also cite research by Sen (2017), which found that Republicans were more sensitive than Democrats to partisan cues when asked to evaluate judicial candidates. Taken in conjunction, these results are consistent with Krishna and Sokolova's (2017) argument that systematic (vs. heuristic) processing of information attenuates the influence of partisan cues—as well as the observation that liberals are more likely than conservatives to engage in systematic processing (Jost, 2017a, 2017b).…”
Section: Theoretical Clarification: the Integration Of “Top‐down” Andmentioning
confidence: 80%
See 4 more Smart Citations
“…Conversely, Democrats were more attentive than Republicans to substantive information about policy content. Krishna and Sokolova (2017) also cite research by Sen (2017), which found that Republicans were more sensitive than Democrats to partisan cues when asked to evaluate judicial candidates. Taken in conjunction, these results are consistent with Krishna and Sokolova's (2017) argument that systematic (vs. heuristic) processing of information attenuates the influence of partisan cues—as well as the observation that liberals are more likely than conservatives to engage in systematic processing (Jost, 2017a, 2017b).…”
Section: Theoretical Clarification: the Integration Of “Top‐down” Andmentioning
confidence: 80%
“…Inspired by the work of Silvan Tomkins (1963), we propose that ideology is a “love affair”—an “elective affinity”—between a person (who possesses a wide range of chronic and temporary needs, interests, and motivations) and a socially constructed, historically situated belief system that offers some opportunity for seduction. Thus, “top‐down” processes of institutional socialization and communication, including exposure to messages from political elites (what Krishna & Sokolova, 2017 refer to as “macro‐level factors”) interact with “bottom‐up” psychological (or “micro‐level”) factors to produce matching (or resonant) ideological outcomes (Jost, Federico, & Napier, 2009). There is nothing “immutable” (or “invariant,” as Oyserman & Schwarz, 2017 suggest) about these outcomes, and there is no non‐tautological sense in which they may be said to spring from “essential differences” between liberal and conservative types of people.…”
Section: Theoretical Clarification: the Integration Of “Top‐down” Andmentioning
confidence: 99%
See 3 more Smart Citations